Forestvoltaics, floatovoltaics and building applied photovoltaics (BAPV) potential for a university campus - Maity, Rittick; Muhammad Khairul Imran, Ahmad Shuhaimi; Sudhakar, Kumarasamy; Amir, Abdul Razak (Tech Science Press, 2024)
The United Nations’ Sustainable Development Goals (SDGs) highlight the importance of affordable and clean energy sources. Solar energy is a perfect example, being both renewable and abundant. Its popularity shows no signs of slowing down, with solar photovoltaic (PV) panels being the primary technology for converting sunlight into electricity. Advancements are continuously being made to ensure cost-effectiveness, high-performing cells, extended lifespans, and minimal maintenance requirements. This study focuses on identifying suitable locations for implementing solar PV systems at the University Malaysia Pahang Al Sultan Abdullah (UMPSA), Pekan campus including buildings, water bodies, and forest areas. A combined technical and economic analysis is conducted using Helioscope for simulations and the Photovoltaic Geographic Information System (PVGIS) for economic considerations. Helioscope simulation examine case studies for PV installations in forested areas, lakes, and buildings. This approach provides comprehensive estimations of solar photovoltaic potential, annual cost savings, electricity costs, and greenhouse gas emission reductions. Based on land coverage percentages, Floatovoltaics have a large solar PV capacity of 32.3 Megawatts (MW); forest-based photovoltaics (Forestvoltaics) achieve maximum yearly savings of RM 37,268,550; and Building Applied Photovoltaics (BAPV) have the lowest CO emissions and net carbon dioxide reduction compared to other plant sizes. It also clarifies the purpose of using both software tools to achieve a comprehensive understanding of both technical and economic aspects.